2021
DOI: 10.3390/laws10030063
|View full text |Cite
|
Sign up to set email alerts
|

Sports, Transgender Rights and the Bodily Politics of Cisgender Supremacy

Abstract: Between 2020 and 2021, one hundred and ten bills in state legislatures across the United States suggested banning the participation of transgender athletes on sports teams for girls and women. As of July 2021, ten such bills have become state law. This paper tracks the political shift towards targeting transgender athletes. Conservative political interests now seek laws that suture biological determinist arguments to civil rights of bodies. Although narrow binary definitions of sex have long operated in the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 93 publications
0
36
1
Order By: Relevance
“…Laws and policies that require people who are transgender to participate in sports based on the sex assigned to them at birth convey that society cannot accept that a person can identify with a gender incongruent to their sex assigned at birth. In their review of proposed state-level transgender sports bans bills in the US, for example, Sharrow found that the bills “rarely explicitly acknowledge the existence of ‘transgender’ people” (p.13) [ 53 ]. Rather, transgender girls and women were misgendered as ‘biological males’ in most bills [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laws and policies that require people who are transgender to participate in sports based on the sex assigned to them at birth convey that society cannot accept that a person can identify with a gender incongruent to their sex assigned at birth. In their review of proposed state-level transgender sports bans bills in the US, for example, Sharrow found that the bills “rarely explicitly acknowledge the existence of ‘transgender’ people” (p.13) [ 53 ]. Rather, transgender girls and women were misgendered as ‘biological males’ in most bills [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their review of proposed state-level transgender sports bans bills in the US, for example, Sharrow found that the bills “rarely explicitly acknowledge the existence of ‘transgender’ people” (p.13) [ 53 ]. Rather, transgender girls and women were misgendered as ‘biological males’ in most bills [ 53 ]. Legislation and policies that require people who are transgender to participate in sports based on sex assigned at birth may also skeptically suggest that a person who wants to participate in sports based on their identified gender is trying to “game the system” for an unfair advantage (e.g., a boy wants to run girl’s track to win state).…”
Section: Discussionmentioning
confidence: 99%
“…This study occurs within a geopolitical Western context in which some conservatives are attempting to police the category “female” (Sharrow 2021), as an oppressive force fuelling anti-trans rhetoric (Hsu 2022). We argue that a focus on the sexed body is bound up in the medicalization of both women’s bodies, childbirth and trans identities whereby trans people who seek perinatal care can be cast under suspicion as not being truly what they claim to be (Gill-Peterson 2014; Thomas 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cis supremacy is understood here as a situation in which cis people hold power over or are privileged over trans people, with trans people systemically disadvantaged. Sharrow (2021) wrote about how institutions are a “site for advancing, enshrining, and normalizing cis-supremacist gender orders” (p. 1). Schools that ignore cis-supremacist hierarchies are complicit in perpetuating, legitimizing, and enabling discrimination (Ferfolja & Ullman, 2021).…”
Section: Trans Inclusion Staged Modelmentioning
confidence: 99%